Navigating Identities of Language Instructors During Remote Teaching in Crisis - Ozcelik, Arzu Ekoc; Gunduz, Zennure Elgun (JOURNAL LANGUAGE TEACHING & LEARNING, 2024)
This study tries to explore the dynamic nature of language teacher identities, interrogating how language instructors perceive and respond to the sudden shift to remote teaching in Turkiye in the aftermath of Kahramanmara & scedil; earthquakes on February 6, 2023. The study also contrasts face-to-face and remote teaching from the perspectives of 124 English language instructors at state and private universities. Data were collected via a survey with 26 Likert-scale statements, 10 rating scale items, and an open-ended question. Descriptive and thematic analyses reveal the complex, multifaceted nature of teacher identities during crises, emphasizing their resilience and adaptability. The findings provide insights for educational policymakers and teacher trainers in supporting language instructors, particularly in emergency remote teaching contexts. By exploring these dynamics, the study contributes to the growing literature on emergency remote teaching and has implications for professional development and support strategies for language instructors facing similar emergency situations.
Keywords: Earthquake; English language teaching; higher education; Language teacher identity; Remote teaching; TEACHERS; Education & Educational Research